2006
DOI: 10.1099/vir.0.82071-0
|View full text |Cite
|
Sign up to set email alerts
|

Ngoye virus: a novel evolutionary lineage within the genus Flavivirus

Abstract: By using degenerate primers deduced from conserved patterns in the flavivirus polymerase gene, a novel RNA virus was discovered in Rhipicephalus ticks sampled from members of the family Bovidae in Senegal. It was named Ngoye virus (NGOV) after the location from which it was isolated. Viral particles could be observed by electron microscopy, but isolation in vertebrate or invertebrate cell lines or by intracerebral infection of newborn mice remained unsuccessful. This is atypical of recognized arboviruses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…In recent years, many novel flaviviruses have been discovered, such as Ngoye virus and New Mapoon virus, along with the earlier-mentioned KRV and a novel strain of CFAV (7,8,16,26). This indicates a much larger heterogeneity among flaviviruses than previously thought and suggests that a large number of distantly related flaviviruses exist.…”
mentioning
confidence: 70%
“…In recent years, many novel flaviviruses have been discovered, such as Ngoye virus and New Mapoon virus, along with the earlier-mentioned KRV and a novel strain of CFAV (7,8,16,26). This indicates a much larger heterogeneity among flaviviruses than previously thought and suggests that a large number of distantly related flaviviruses exist.…”
mentioning
confidence: 70%
“…Munz et al (1987) discovered reoviruslike particles in the R. appendiculatus cell line RA243; their presence did not prevent replication of the bunyavirus NSDV. Using a PCR-based method, Grard et al (2006) identified a novel flavivirus in R. evertsi and Rhipicephalus guilhoni ticks collected from small ruminants in Senegal; Ngoye virus failed to replicate in a range of vertebrate and invertebrate cell lines, including lines derived from embryonic R. appendiculatus and I. scapularis. Propagation of this virus in the recently established R. evertsi cell lines (Table 1) could be attempted to investigate its host species specificity and whether it is another candidate ''tick-only virus.''…”
Section: Tick Cell Culture and Arbovirusesmentioning
confidence: 99%
“…Interestingly, some of these ISFs appear to be capable of integrating their genomic sequences into mosquito genomes (Crochu et al, 2004). The additional flaviviruses, Tamana bat virus (TABV) (de Lamballerie et al, 2002) and Ngoye virus (Grard et al, 2006) appear to represent highly divergent genetic lineages not closely associated with any currently recognized flavivirus group.…”
Section: Introductionmentioning
confidence: 99%